2018
DOI: 10.1002/ajh.25053
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic hematopoietic stem cell transplant overcomes the adverse survival effect of very high risk and unfavorable karyotype in myelofibrosis

Abstract: The prognostic importance of genetic information in primary myelofibrosis (PMF) was recently highlighted in a study of over 1000 cytogenetically-annotated patients; 5-year survival rates were 8% for very high risk (VHR), 27% "unfavorable" and 45% "favorable" karyotype. The current study addresses the practice-relevant question of whether or not allogeneic hematopoietic stem cell transplant (HCT) can overcome the detrimental survival effect of VHR or unfavorable karyotype. The study included 67 patients with PM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 25 publications
1
38
1
1
Order By: Relevance
“…Within the MTSS study, current cytogenetic risk stratifications according to DIPSS‐plus and MIPSS70‐plus (version 2.0) showed no difference in outcome, whereas it has been previously shown that allo‐HCT can overcome the negative effect of poor‐risk cytogenetics in patients with myelofibrosis . In contrast, a recent study showed that unfavorable and very high‐risk karyotypes (single/multiple abnormalities of −7, i(17q), inv(3)/3q21, 12p−/12p11.2, 11q−/11q23, +21, or other autosomal trisomies, not including +8/+9) resulted in similar OS, whereas favorable karyotype showed better OS compared with both groups .…”
Section: Cytogeneticsmentioning
confidence: 93%
“…Within the MTSS study, current cytogenetic risk stratifications according to DIPSS‐plus and MIPSS70‐plus (version 2.0) showed no difference in outcome, whereas it has been previously shown that allo‐HCT can overcome the negative effect of poor‐risk cytogenetics in patients with myelofibrosis . In contrast, a recent study showed that unfavorable and very high‐risk karyotypes (single/multiple abnormalities of −7, i(17q), inv(3)/3q21, 12p−/12p11.2, 11q−/11q23, +21, or other autosomal trisomies, not including +8/+9) resulted in similar OS, whereas favorable karyotype showed better OS compared with both groups .…”
Section: Cytogeneticsmentioning
confidence: 93%
“…Current treatment modalities in PMF, other than allogeneic hematopoietic stem cell transplant (alloSCT), do not modify the natural history of the disease and have not been shown to improve survival, which is estimated at median 6 years; palliative treatment modalities in PMF include JAK2 inhibitors, hydroxyurea, immunomodulatory drugs, androgen preparations, corticosteroids, involved‐field radiation and splenectomy . Unfortunately, alloSCT in PMF is a risky procedure with nontrivial risk of treatment‐related death and comorbidity, such as graft vs host disease (GVHD) and chronic immunosuppression from drugs used to prevent graft rejection or prevent or alleviate GVHD . Accordingly, for the individual patient, risk‐benefit analysis is required to select patients who are most appropriate for early transplant and this is often accomplished by the use of contemporary risk models …”
Section: Introductionmentioning
confidence: 99%
“…Genomicallydriven models are likely to outperform clinical models in identifying transplant candidates given the disease-specific nature of the model, though this only holds true if the prognostic risk factors are sensitive to immune-based therapies, such as AHSCT. Recent studies have suggested that AHSCT can overcome high-risk disease in terms of cytogenetics17 and high-risk somatic mutations,18 however, larger studies are needed to confirm and refine these findings since all high-risk genomic findings are unlikely to be equally sensitive to transplant.…”
mentioning
confidence: 99%